2018
DOI: 10.1002/chem.201705889
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Energy Electron‐Induced Strand Breaks in Telomere‐Derived DNA Sequences—Influence of DNA Sequence and Topology

Abstract: During cancer radiation therapy high-energy radiation is used to reduce tumour tissue. The irradiation produces a shower of secondary low-energy (<20 eV) electrons, which are able to damage DNA very efficiently by dissociative electron attachment. Recently, it was suggested that low-energy electron-induced DNA strand breaks strongly depend on the specific DNA sequence with a high sensitivity of G-rich sequences. Here, we use DNA origami platforms to expose G-rich telomere sequences to low-energy (8.8 eV) elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 54 publications
1
43
0
Order By: Relevance
“…The comparison of the obtained cross sections for SSBs is visualized in Figure C. The lowest cross section for SSBs was obtained for 5′‐d(G 12 ) with a value of (3.1±0.2) ⋅ 10 −15 cm 2 while the other cross sections for SSBs of 5′‐d(X 12 ) X=A, C, T are very similar and vary from (3.4±0.5) to (3.9±0.4) ⋅ 10 −15 cm 2 . In Table it can be seen that these results are in a very good agreement and in the same dimension like experiments done so far with oligonucleotides in this energy range ,. Boudaïffa et al .…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…The comparison of the obtained cross sections for SSBs is visualized in Figure C. The lowest cross section for SSBs was obtained for 5′‐d(G 12 ) with a value of (3.1±0.2) ⋅ 10 −15 cm 2 while the other cross sections for SSBs of 5′‐d(X 12 ) X=A, C, T are very similar and vary from (3.4±0.5) to (3.9±0.4) ⋅ 10 −15 cm 2 . In Table it can be seen that these results are in a very good agreement and in the same dimension like experiments done so far with oligonucleotides in this energy range ,. Boudaïffa et al .…”
Section: Resultssupporting
confidence: 84%
“…Comparing G rich sequences (Table ) it is demonstrated that 5′‐d(TT(GGG ATT) 2 T) with σ(5′‐d(TT(GGG ATT) 2 T))=(6.8±0.5) ⋅ 10 −15 cm 2[11] has a higher cross section for SSBs than 5′‐d(G 12 ) followed by 5′‐d(TGT GTG A) 2 T). An A base located next to a G‐stack leads to a polarization with a partial positive charge on the G stack, which can result in an increased cross section for LEE induced SSBs, which is even higher than the cross section found for d(G 12 ). This is reasonable considering that the 5′‐d(G 12 ) sequence is most likely not polarized.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations